HUMAN SCIENCE DALAM FILSAFAT ISLAM - David, Abadi (JOURNAL J-MPI : JURNAL MANAJEMEN PENDIDIKAN, PENELITIAN DAN KAJIAN KEISLAMAN, 2024)
This study examines the relevance of human science concepts in Islamic philosophy to the modern context. Using historical approaches and interdisciplinary analysis, this research explores the classical thoughts of Islamic philosophers such as Al-Farabi, Ibn Sina, and Al-Ghazali on human concepts, ethics, morality, and epistemology. The research method employed is literature study from books, journals, and other relevant sources. The results show that these concepts remain relevant and can be applied in education, professionalism, and personal life to shape holistic and ethical individuals. The conclusion emphasizes the importance of integrating classical and modern thoughts to develop a more holistic approach in addressing contemporary challenges. Further research is suggested to deepen the understanding of the relationship between classical and contemporary thoughts